Comparison of Energy Expenditure Assessed Using Wrist- and Hip-Worn ActiGraph GT3X in Free-Living Conditions in Young and Older Adults - Guediri, Amine; Robin, Louise; Lacroix, Justine; Aubourg, Timothee; Vuillerme, Nicolas; Mandigout, Stephane (Frontiers in Medicine, 2021)
The World Health Organization has presented their recommendations for energy expenditure to improve public health. Activity trackers do represent a modern solution for measuring physical activity, particularly in terms of steps/day and energy expended in physical activity (active energy expenditure). These activity trackers can be worn on a variety of locations on the body, mainly at the wrist and the hip, in an undifferentiated way according to the manufacturer’s instruction. The aim of this study was to compare the absolute error rate of active energy expenditure assessed using a wrist- and hip-worn ActiGraph GT3X+ over a 24-h period in free-living conditions in young and older adults. To achieve this goal, 22 young adults and 22 older adults were asked to wear two ActiGraph GT3X+ simultaneously at two locations recommended by the manufacturer; i.e., one positioned around the wrist and one above the hip, over a 24-hour period. Freedson algorithm was applied for data analysis. For both groups, the absolute error rate tended to decrease from 1252% to 43% for older adults and from 408% to 46% for young participants for higher energy expenditure. Interestingly, for both young and older adults, the wrist-worn ActiGraph provided a significantly higher active energy expenditure (943 +/- 264 cal/min) than the hip-worn (288+/- 181 cal/min). Taken together, these results suggest that caution is needed when using active energy expenditure as an outcome to quantify physical activity.